2010
DOI: 10.1038/nature09596
|View full text |Cite
|
Sign up to set email alerts
|

A ground-based transmission spectrum of the super-Earth exoplanet GJ 1214b

Abstract: In contrast to planets with masses similar to that of Jupiter and higher, the bulk compositions of planets in the so-called super-Earth regime (M p = 2 -10 M ⊕ ) cannot be uniquely determined from a mass and radius measurement alone. For these planets, there is a degeneracy between the mass and composition of the interior and a possible atmosphere in theoretical models 1, 2 . The recently discovered transiting super-Earth GJ 1214b is one example of this problem 3 . Three distinct models for the planet that are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
432
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(459 citation statements)
references
References 22 publications
26
432
1
Order By: Relevance
“…This framework is empirically motivated, as the data show that simply dividing the target light curve by the sum of the comparison light curves removes most of the variations in the out-of-transit flux from the target, leaving only a smoothly varying long-term trend. Like Bean et al (2010), we find that this trend can be modeled well as a second order polynomial function of time, and attribute it to the color difference between this very red target star and the available comparison stars in the field. In this framework, the target light curve can be expressed as…”
Section: Polynomial-based Modeling Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…This framework is empirically motivated, as the data show that simply dividing the target light curve by the sum of the comparison light curves removes most of the variations in the out-of-transit flux from the target, leaving only a smoothly varying long-term trend. Like Bean et al (2010), we find that this trend can be modeled well as a second order polynomial function of time, and attribute it to the color difference between this very red target star and the available comparison stars in the field. In this framework, the target light curve can be expressed as…”
Section: Polynomial-based Modeling Frameworkmentioning
confidence: 99%
“…Starting with the first results provided by Bean et al (2010), observations of GJ1214b in the optical and near-infrared have found a featureless spectrum Crossfield et al 2011;Désert et al 2011;Berta et al 2012;Murgas et al 2012;Colón & Gaidos 2013;de Mooij et al 2013;Fraine et al 2013;Teske et al 2013;Cáceres et al 2014;Gillon et al 2014;Wilson et al 2014;Nascimbeni et al 2015). Reported spectral features in the near-infrared (Croll et al 2011;de Mooij et al 2012) have not been reproduced by follow-up measurements in the same bandpasses (Narita et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique was pioneered by Bean, Miller-Ricci Kempton & Homeier (2010), using the VLT to produce a transmission spectrum of the super-Earth GJ 1214b. Such observations have benefited not only from advances in observing strategy, but also from the availability of new bright targets with nearby comparison stars.…”
Section: Introductionmentioning
confidence: 99%